Nature vs policy: drought and famine in the northeast of Brazil, 1877-79 - Tiburcio, James Augusto Pires (Sustainability in Debate, 2021)
Droughts followed by famines were common in Brazil, mainly in Northeast Brazil, until the 1980s and were frequently devastating, destroying livelihoods. A succession of droughts resulted in harvest failure, triggering famines in some cases. Famine-like conditions prevailed mainly in the 1877-79 Grande Seca (Great Drought), in which many died of malnutrition-related causes. In subsequent droughts, famine-like conditions reoccurred, but the extent of starvation-induced deaths declined to almost zero. Do only available political theories and known natural and socio-political factors, such as climate, topography, and market viability, provide sufficient data to investigate the causes of the drought of 1877-1879? The author concludes that there is little or no research, accumulated knowledge and information on the possible factors that satisfactorily explain why the drought and famine episodes were so impactful in that period.